Analysis and availability of monthly maps of the Temperature and Humidity Index (THI) for Southeastern Brazil - Andrade , Ricardo Guimarães; Garcia, Lucas Cantarino Soares; Hott, Marcos Cicarini; Junior, Walter Coelho Pereira de Magalhães; Peixoto, Maria Gabriela Campolina Diniz; Pires, Maria de Fatima Ávila; Facco, Alexandro Gomes (Seven Editora, 2023)
Brazil is among the five largest milk producers in the world. In 2021 the national production was 35.3 billion liters of milk, of this total, 34% refers to milk produced in the Southeast region. Although the Southeast stands out in the national ranking by Regions, its average productivity is still considered low. The Temperature and Humidity Index (UTI) has been widely used in research involving the evaluation of thermal comfort conditions related to animal performance. This study aimed to analyze and make available monthly maps of UTI for the Southeast of Brazil. Air temperature and humidity data from INMET's automatic stations, from January 2007 to December 2021, were analyzed for consistency and possible failures of observational records were corrected. Subsequently, the UTI was estimated and geoprocessing techniques were applied to generate and make available the maps of monthly UTI averages for the Southeast of Brazil. According to the results presented in the maps, it is observed the predominance of the UTI class ≤ 70 between the months of May and September. In addition, it is noted that classes of high UTI values prevail in the months of December to March, indicating an environment condition not conducive to the thermal comfort of cattle. DOI:https://doi.org/10.56238/Connexpemultidisdevolpfut-047